2009
DOI: 10.1111/j.1444-0938.2009.00401.x
|View full text |Cite
|
Sign up to set email alerts
|

Refraction, intraocular pressure and anterior chamber depth changes after Nd:YAG laser treatment for posterior capsular opacification in pseudophakic eyes

Abstract: Purpose:The aim was to investigate the effect of Nd:YAG capsulotomy on refraction, intraocular pressure and anterior chamber depth changes and complications of Nd:YAG laser treatment for posterior capsular opacification in pseudophakic eyes. Methods: Our study includes 26 eyes (23 patients) with posterior capsular opacification after uncomplicated phacoemulsification surgery and intraocular lens implantation. Complete ocular examinations were performed for all patients. The visual acuity, intraocular pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
29
4
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 7 publications
3
29
4
4
Order By: Relevance
“…Waseem and Khan reported that higher YAG laser energy had significantly higher chances of raising IOP. Similar to our results, in most of the studies, significant IOP elevations were not observed after Nd‐YAG laser posterior capsulotomy .…”
Section: Discussionsupporting
confidence: 92%
“…Waseem and Khan reported that higher YAG laser energy had significantly higher chances of raising IOP. Similar to our results, in most of the studies, significant IOP elevations were not observed after Nd‐YAG laser posterior capsulotomy .…”
Section: Discussionsupporting
confidence: 92%
“…Keratometric astigmatism and spherical equivalents did not change after capsulotomy, whereas cylindrical errors decreased. There are various reports on the effects of Nd:YAG capsulotomy on refraction, finding no change or a hyperopic shift in spherical equivalents; however, in none of the prior studies analysing the refractive changes due to Nd:YAG capsulotomy were the refractive powers evaluated separately as spherical and cylindrical errors. Spherical equivalents may conceal the real refractive alterations due to changes in cylindrical power.…”
Section: Discussionmentioning
confidence: 98%
“…Increased IOP following YAG is the most common complication; despite prophylactic treatment its incidence was observed as between 15%-30% in some studies (18,19) . The short-and long-term results are unclear in studies (19)(20)(21) examining IOP changes after YAG capsulotomy. Whether or not the choroid is influenced as a result of pressure fluctuations after YAG capsulotomy should therefore be subject to scrutiny.…”
Section: Discussionmentioning
confidence: 99%